Diversity among agrobacteria isolated from diseased plants of blueberry (Vaccinium corymbosum) in Argentina - Alippi, Adriana Mónica (2012)
The aim of this study was to isolate, identify and analyze the diversity of the causative agents of crown galls and hairy roots from symptomatic plants of Vaccinium corymbossum by means of biological, biochemical and molecular tools. All the bacteria isolated from blueberries (n = 78) were found to be Agrobacterium since they grew on three differential media, provoked cell and/or root proliferation on Kalanchoe, and contained a 730 bp partial sequence that codes for virulence genes within the virC operon found on Ti and/or Ri plasmids. Isolates were highly variable considering the ERIC-PCR patterns as well as biochemical reactions and were all represented by 7 different restriction patterns of the 16SrDNA. While most of the isolates belonged to Agrobacterium bv. 1 (n = 33) or Agrobacterium bv. 2 (n = 31) only fourteen were Agrobacterium rubi. A representative isolate of each of these three groups was further identified by sequencing the approximately 400 bp 16SrDNA. We concluded that Vaccinium plants are particularly susceptible to Agrobacterium bv. 1, Agrobacterium bv. 2, and also to Agrobacterium rubi. To our knowledge this is the first survey of Agrobacterium affecting blueberries in Argentina.